Pembuatan lembar kerja peserta didik (LKPD) berbasis model discovery learning pada materi gelombang berbantuan aplikasi android untuk kelas XI SMA/MA - Helena Pentury; Festiyed Festiyed; Hamdi Hamdi; Yurnetti Yurnetti (PILLAR OF PHYSICS EDUCATION, 2019)
The purpose of this research is to produce LKPD based on discovery learning models in wave topic assisted by android applications that are feasible for physics learning class XI, and determine the feasibility of LKPD based on discovery learning models assisted with android applications. This research focuses on making LKPD products according to the manufacturing steps based on the modified Ministry of National Education (2010). The research conducted was twice the validity test of LKPD by four validators, consisting of three lecturers from the Department of Physics UNP and one teacher from Bukittinggi High School 5. The results of this study are in the form of making LKPD based on discovery learning models assisted by android applications that are suitable for use in the learning process. When seen from the results of the validity test, the value of the validity 1 is 80 (%) and the validity 2 is 86 (%). Based on the results of the two validity tests it can be concluded that the LKPD made in this study is suitable for use in physics learning for class XI SMA / MA.